Influence of dietary hydrolyzed cottonseed protein supplementation on physiology and metabolism of Japanese quails - Moradpour, H; Kheiri, F; Faghani, M; Landy, N (Journal of the Hellenic Veterinary Medical Society, 2024)
The current study was carried out to examine the effects of dietary supplementation of cottonseed protein hydrolysate (CPH) as an alternative to in-feed antibiotics on growth performance, carcass characteristics, immunity, jejunum morphology, coliform bacteria of ileum, and total antioxidant capacity (T-AOC) of serum in Japanese quails. A total of one hundred and ninety two 7-day-old mixed-sex broiler quails (Coturnix japonica) were allotted to 6 treatments with 4 replicates. Four dietary were formulated to contain 0 (basal diet as a control), 5, 6, and 7 g CPH/kg of diet in comparison with basal diet + 15 IU vitamin E/kg or basal diet + 2 mg lincomycin. At 35 d of age final body weights of broiler quails were not significantly affected by the dietary treatments although it tended to increase in broiler quails supplemented with vitamin E or 5 g CPH/kg of diet (P > 0.05). The FCR of broiler quails fed diets containing antibiotic was significantly improved (P < 0.05). The relative weight of bursa of fabricius was significantly higher in broiler quails supplemented with 5 g CPH/ kg of diet (P < 0.05). The broiler quails fed diets containing antibiotic or 7 g CPH/kg of diet had significantly lower coliform counts (P < 0.05). The T-AOC of serum was higher in boiler quails fed diets supplemented with vitamin E or different levels of CPH compared to those fed basal diet (P < 0.05). In conclusion the findings of the present study indicated that supplementation of 5 g CPH/kg of diet could induce favorable influences on coliform counts and T-AOC of serum and it can be used in broiler quails diet as an alternative for in-feed antibiotics.